Leading with Executive Presence: Strategies for Effective Leader ship - Raghunath Reddy Koilakonda (North American Journal of Engineering Research, 2023)
Creating a strong executive presence is essential for effective leadership and efficiency in the hectic world of contemporarycompany operations. Leaders possessing executive presence not only instill trust and legitimacy but also cultivate an excellence-oriented culture inside their teams and organizations. To foster executive presence, this study explores a variety of tactics derivedfrom leadership theory and real-world applications. A few of the important topics covered are how to effectively communicate,how to remain composed under duress, how important authenticity is in leadership, and how to establish long-lasting credibility.This study aims to give leaders who want to increase their impact and promote long-term growth in their organizations a solidframework by analyzing case studies and examples. Through the acquisition of these tactics, leaders can augment their ownleadership proficiencies and facilitate the establishment of a vibrant workplace environment that fosters creativity, collaboration,and achievement.